Konsep Insan Kamil sebagai Strategi Pengembangan SDM Guru di Era Society 5.0: Perspektif Islamic Human Resource Management - Zainal Abidin; Syahrial Shaddiq; Khuzaini (PT. Saha Kreasi Indonesia, 2025)
The era of Society 5.0 has brought rapid changes to the field of education, requiring teachers not only to master technology but also to possess strong spiritual, moral, and humanistic character. At the same time, various challenges—such as low digital literacy, integrity crises, and insufficient pedagogical readiness—remain major issues in the development of teacher human resources (HR) in Indonesia. This study aims to propose the concept of Insan Kamil as a strategic framework for developing teacher HR from the perspective of Islamic Human Resource Management (IHRM). This research employs a qualitative approach through a literature review by examining the concept of Insan Kamil in the Qur’an, hadith, classical Islamic literature, as well as modern theories on teacher HR and Society 5.0. The findings indicate that the Insan Kamil concept—which encompasses spiritual (ruhaniyah), intellectual (aqliyah), moral (akhlaqiyah), and practical (amaliyah) dimensions—is highly relevant to addressing teacher competency challenges in the digital era. This concept emphasizes the development of spirituality, professional ethics, digital literacy, and pedagogical productivity. Integrating the values of Insan Kamil into IHRM produces a holistic, sustainable, and human-centered model for teacher HR development that balances technological advancement with Islamic humanistic values. Therefore, the Insan Kamil framework can serve as a comprehensive alternative strategy to empower teachers in responding to educational challenges in the Society 5.0 era.